PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SEJAHTERA LILYANA JAYA - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
The study was conducted at PT. Lilyana Sejahtera Jaya in Pekanbaru. Based on the research background mentioned above, the writer can formulate the problem in this research is How organosasi cultural influence on the performance of employees at PT. Lilyana Sejahtera Jaya. PT. Lilyana Sejahtera Jaya in Pekanbaru. The purpose of this research was to determine the effect of culture on employee performance organisasiterhadap employees at PT. SEJAHTERA LILYANA .The data analysis in this research by using descriptive and quantitative methods. Methods descriptive analysis of data by the decomposition of the theories contained in the bibliography, and are associated with the data obtained from the research that will be collected, classified and tabulated then be concluded. And quantitative methods with simple linear regression techniques.Samples taken in this study is numbered 52 people, the results obtained by simple linear regression equation is as follows: Y = 15 733 + 0.827X. It was therefore concluded simple regression results above, it can be concluded that the direction of the relationship shared by all the independent variables on the dependent variable has a positive relationship direction, that is, if the independent variable increases one-unit then the dependent variable will increase by units of coefficient of determination R_ Square obtained for 0512. This means that 51.2% of variable performance of employees affected by organizational culture variable, while the remaining 48.8% is influenced by other variables not examined in this study.